Evaluation and selection of alfalfa genotypes for tolerance to aluminium toxic stress - Liatukienė, Aurelija; Skuodienė, Regina; Norkevičienė, Eglė; Tamm, Sirje; Pechter, Priit; Petrauskas, Giedrius (Frontiers in Plant Science, 2024)
Alfalfa is one of the most important and the most cultivated crop due to its high nutritive quality and yield, but adaptation of alfalfa genotypes differ in terms of mobile aluminium stress in the soil. The aim of this study was to evaluate the tolerance to mobile Al concentrations in the laboratory and in the naturally acidic soil and select the promising genotypes based on agro-biological traits. In 2019, a laboratory experiment was conducted at the Institute of Agriculture of LAMMC. The experiment in the acidic soil with different mobile Al concentrations was conducted at the Vėžaičiai Branch of LAMMC. In 2020, the crops of alfalfa genotypes (11 cultivars and 3 populations) were established on Balthygleyic Dystric Retisol. The agro-biological traits were assessed during the 2021–2022 season. The tolerance index of hypocotyls and roots was evaluated using the filter-based screening method at different AlCl3 (0.0–64 mM) concentrations. The study results of the filter-based screening method showed that the genotype Žydrūnė, Malvina, Jõgeva 118, Skriveru, and 3130 were the most tolerant ones and the hypocotyl tolerance index of these genotypes was higher compared to medium tolerant genotypes Birutė, PGR12489, Europe and AJ2024 at 8, 16, 32 and 64 mM AlCl3 concentrations. The hypocotyl and root tolerance index of medium tolerant genotypes was higher compared to a sensitive genotype PGR10249 at 8 and 16 mM AlCl3. The study of cluster analysis with mobile Al 0.0–65.0 mg kg-1 showed that the genotypes Žydrūnė, Europe, AJ2024 and 3130 were the best in terms of wintering and spring regrowth, the cultivar Malvina had the best value of wintering, height before flowering and stem number, the cultivar Birutė had the best value of spring regrowth, height before flowering and seed yield, and the cultivar Skriveru had the best value of spring regrowth, height before flowering, stem number and seed yield.